Maternal Age and Length of Work Influencing Breastfeeding Self Efficacy in Primiparous Pregnant Women at Istri Utami Midwifery care - Nurul Kurniati; Siti Nurhidayati (Universitas 'Aisyiyah Yogyakarta, 2020)
Nutrition Monitoring in 2016 shows that coverage of exclusive breast milk 54.0% below the national target of 80%. Breastfeeding self efficacy score measurement to predict mother's belief in giving brest milk. This research aims to know the influence of maternal age and long work with breastfeeding self efficacy This research used survey method with cross sectional approach , population and sample 64 pregnant women in third trimester, primipara both working and not working, sampling using accidental sampling and questionnaire instrument retrieval data using BSE-SF (Breastfeeding Self Efficacy-Short Form) at Istri Utami Midwifery care. The results of the study proved a statistically significant test showing that there was a relationship between age and length of work with Breastfeeding self efficacy in third trimester of pregnant women with p-value 0.022 0.05 and p-value 0.002 0.05. Multivariate statistical test results obtained for lenght work has the most significant relationship of these two factors. Length works have smallest value of p 0.002 (Exs β = 6,153). Health Technology Assessment (HTA), use of BSE-SF in health service as maternal readiness screening in breastfeeding, support strategy formation in place works to create an environment and time support to increase the duration of breastfeeding in mothers working.